Study of the quality of life in amputee soccer players - Auricchio, José Ricardo; Bernardes, Nathalia; Moreno, Marlene Aparecida (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: Although a number of aspects related to amputation have a negative impact on quality of life, sports can prevent disease and promote health in this population just as it can among the nondisabled. Objective: The aim of this study was to evaluate the quality of life in amputee soccer players (n=25). Method: We compared scores on the World Health Organization Quality-of-Life Scale (WHOQOL-BREF). Results: observing that the physical (PHY: 71±16), psychological (PSY: 76±18) and social domains (SOC: 72±22) showed higher values (p <0.05) than the environment domain (ENV: 55±17). There was a positive correlation between PHY and PSY (r: 0.8), PHY and SOC (r: 0.7) and PHY and ENV (r: 0.7). Moreover, PHY showed a positive correlation with SOC (r: 0.9) and ENV (r: 0.8). In addition, the adapted sport improved the overall quality of life index (GQOLI= 71.50). Conclusion: These results show that amputee soccer improves the quality of life of its players.